2021
DOI: 10.1155/2021/5531988
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Study of MEBO Combined with Jinhuang Powder for Diabetic Foot with Infection

Abstract: Background. To investigate the efficacy and safety of MEBO combined with Jinhuang powder for the treatment of diabetic foot with infection. Methods. From August 2015 to August 2019, patients with diabetic foot in our hospital were divided into the treatment group and control group. The treatment group was treated with moist exposed burn ointment (MEBO) combined with Jinhuang powder, while the control group was treated with MEBO only. Results. After one week of treatment, the effective rate in the treatment gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 12 publications
0
24
0
Order By: Relevance
“…e liquid medicine is brought into the eye of the needle with the needle tip, irritating the skin and causing bleeding [7]. [8].…”
Section: How To Use Jinhuang Powder 8 G Of Jinhuang Powdermentioning
confidence: 99%
“…e liquid medicine is brought into the eye of the needle with the needle tip, irritating the skin and causing bleeding [7]. [8].…”
Section: How To Use Jinhuang Powder 8 G Of Jinhuang Powdermentioning
confidence: 99%
“…A total of 657 distinctive studies were found, of which 25 studies (between 1988 and 2022) satisfied the inclusion criteria and were comprised in the study. 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 The 25 studies included 1777 subjects with cancer‐related symptoms at the start of the study; 953 of them were provided with Chinese herbal medicines and 824 were control. All studies evaluated the influence of Chinese herbal medicines on cancer‐related pressure ulcer wounds, fatigue, constipation, and anorexia.…”
Section: Resultsmentioning
confidence: 99%
“…This meta‐analysis study based on 25 studies included 1777 subjects with cancer‐related symptoms at the start of the study; 953 of them were provided with Chinese herbal medicines and 824 were control. 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 Chinese herbal medicines had significantly higher effectiveness in treating pressure ulcer wound, fatigue, and constipation compared to control in subjects with cancer‐related symptoms. However, Chinese herbal medicines had no significant effect on treating anorexia compared to control in subjects with cancer‐related symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…This is a comment on “This is a comment on “Clinical Study of moist exposed burn ointment (MEBO) Combined with Jinhuang powder for Diabetic Foot with Infection”[ 1 ]. We were pleased that read the research article by Hong-Bo Zhan, et al [ 1 ].…”
Section: To the Editormentioning
confidence: 99%
“…This is a comment on “This is a comment on “Clinical Study of moist exposed burn ointment (MEBO) Combined with Jinhuang powder for Diabetic Foot with Infection”[ 1 ]. We were pleased that read the research article by Hong-Bo Zhan, et al [ 1 ]. Their work highlights that the use of Jinhuang powder as supplement combined with MEBO as an effective and safe therapy for diabetic foot.…”
Section: To the Editormentioning
confidence: 99%